Pembelajaran Deep Learning sebagai Strategi Penguatan Literasi Membaca Siswa Sekolah Dasar pada Era Kurikulum Merdeka - Dedy Irawan; Adam Latuconsina; Wahyu Laraswati; Muslim Muslim (Walada: Journal of Primary Education, 2026)
Reading literacy is a fundamental competency that supports elementary school students in understanding information, developing critical thinking skills, and constructing knowledge meaningfully. However, reading instruction in elementary schools is still frequently oriented toward memorization and literal comprehension, resulting in limited higher-order thinking abilities among students. This study aims to analyze deep learning as a strategy for strengthening reading literacy among elementary school students in the era of the Merdeka Curriculum. The study employed a qualitative descriptive approach using the literature study method. Data sources were obtained from national and international scientific articles indexed in Google Scholar, ERIC, Scopus, and Garuda databases published between 2017–2026. From the initial search results, 18 relevant articles were selected and analyzed using content analysis techniques through data reduction, data presentation, and conclusion drawing. The findings indicate that deep learning contributes positively to the improvement of reading comprehension, critical thinking skills, reflective learning, and student engagement in literacy activities. The implementation of strategies such as Problem Based Learning (PBL), Higher Order Thinking Skills (HOTS)-based learning, contextual learning, reflective learning, and digital literacy integration supports more meaningful and student-centered literacy learning. Therefore, deep learning can be considered a relevant pedagogical strategy for strengthening reading literacy in elementary schools in accordance with the objectives of the Merdeka Curriculum